Concerns of older patients and their caregivers in the emergency department. - Noortje Zelis; Sarah E Huisman; Arisja N Mauritz; Jacqueline Buijs; Peter W de Leeuw; Patricia M Stassen (PLoS ONE)
Background Older emergency department (ED) patients often have complex problems and severe illnesses with a high risk of adverse outcomes. It is likely that these older patients are troubled with concerns, which might reflect their preferences and needs concerning medical care. However, data regarding this topic are lacking. Methods This study is a sub study of a prospective, multicenter, observational cohort study among older medical ED patients (≥65 years). Patients or their caregivers were asked about their illness-related concerns during the first stage of the ED visit using a questionnaire. All concerns were categorized into 10 categories, and differences between patients and caregivers, and between age groups were analyzed. Odds Ratios were calculated to determine the association of the concerns for different adverse outcomes. Results Most of the 594 included patients (or their caregivers) were concerned (88%) about some aspects of their illness or their need for medical care. The most often reported concerns were about the severity of disease (43.6%), functional decline (9.4%) and dying (5.6%). Caregivers were more frequently concerned than patients (p<0.001) especially regarding the severity of disease (50.5 vs 39.6%, p = 0.016) and cognitive decline (10.8 vs. 0.3%, p <0.001). We found no difference between age groups. The concern about dying was associated with 30-day mortality (OR 2.89; 95%CI: 1.24-6.70) and the composite endpoint (intensive- or medium care admission, length of hospital stay >7 days, loss of independent living and unplanned readmission within 30 days) (OR 2.32; 95%CI: 1.12-4.82). In addition, unspecified concerns were associated with mortality (OR 1.88; 95%CI: 1.09-3.22). Conclusion The majority of older patients and especially their caregivers are concerned about their medical condition or need for medical care when they visit the ED. These concerns are associated with adverse outcomes and most likely reflect their needs regarding medical care. More attention should be paid to these concerns because they may offer opportunities to reduce anxiety and provide care that is adjusted to their needs. Trial registration This study was registered on clinicalTriagls.gov (NCT02946398).